Health Counseling on Nutrition-Conscious Families (Kadarzi) in Sidodadi Ramunia Village - Arisman, Yessy; Era Liesmayani, Elvi; Citra Hariati, Mayang (JURNAL PENGMAS KESTRA (JPK), 2023)
Family Aware Nutrition (KADARZI) has become a crucial initiative in efforts to improve public health at the family level. This program focuses on increasing understanding and awareness of nutrition within the family by providing knowledge, prevention, and solutions to nutritional problems. Through families who have an understanding and are aware of the nutritional status of the family, it is hoped that morbidity and mortality rates will be reduced, because one of the efforts to improve health status by improving nutritional status. Sidodadi Village is the location for the implementation of KADARZI counseling activities. The media used for this counseling include laptops, infocus, and microphones to achieve optimal results. 20 community members of Sidodadi Village participated in this activity involving education on the concept of Nutrition Conscious Family, supported by discussion sessions and practical demonstrations. The results of the evaluation of activities showed a significant increase in public understanding related to KADARZI, with an initial knowledge level of 15% which jumped to 90%. This achievement reflects the positive impact provided by extension activities on public knowledge about KADARZI. Increasing nutrition awareness is expected to have a positive impact on the overall nutritional status in the Sidodadi Village community. The success of this program illustrates the urgency of education in shaping healthy behaviors, becoming the basis for positive change in family daily life. Therefore, KADARZI is not only a preventive measure, but also a long-term investment in the health of local communities, bringing sustainable benefits to future generations.